2003
DOI: 10.1002/nag.287
|View full text |Cite
|
Sign up to set email alerts
|

Large displacement FEM modelling of the cone penetration test (CPT) in normally consolidated sand

Abstract: SUMMARYA new finite element model based on a large strain formulation has been developed to study cone penetration in normally consolidated sand. An auto-adaptive remeshing technique was utilized for handling the very large distortion of sand surrounding the cone tip. A frictional contact interface utilizing Mohr-Coulomb's theory was chosen to represent interactions between the surface of the cone and sand. To model the sand behaviour, the non-associated Drucker-Prager constitutive model was selected. ABAQUS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 28 publications
0
35
0
2
Order By: Relevance
“…Susila and Hryciw (2003), Huang et al (2004) and Liyanapathirina (2009) considered the use of large-strain FEM analysis to examine cone penetration in normally consolidated soils. Contact elements were used at the soil-pile interface to allow penetration to large depths to be achieved, and to investigate the effect of soil properties such as φ on the q c value.…”
Section: Recent Developments In Computer Technology Have Led To the Amentioning
confidence: 99%
“…Susila and Hryciw (2003), Huang et al (2004) and Liyanapathirina (2009) considered the use of large-strain FEM analysis to examine cone penetration in normally consolidated soils. Contact elements were used at the soil-pile interface to allow penetration to large depths to be achieved, and to investigate the effect of soil properties such as φ on the q c value.…”
Section: Recent Developments In Computer Technology Have Led To the Amentioning
confidence: 99%
“…Examples include [7,8,9,10,11,12], but the employed methods reveal two limitations when applied to penetration into sand. First, common algorithms for node relocation are not qualified to smooth the non-convex mesh regions that inevitably occur during penetration of blunt bodies.…”
Section: Introductionmentioning
confidence: 99%
“…As the cone advances into the soil, it is generally assumed that the cone penetration force estimates the relative soil strength at a particular depth. Researchers have shown that the point cone penetration force is influenced by the soil properties in the zone of influence (Gill, 1968;Sanglerat, 1972;Mulqueen et al, 1977;Lunne et al, 1997;and Susila and Hryciw, 2003). According to Lunne et al (1997), the zone of influence depends on layering and soil material stiffness that it can reach up to 10 to 20 times the cone diameter for stiff soil material.…”
Section: Introductionmentioning
confidence: 99%